Comparative evaluation of Menz and Awassi x Menz crossbred sheep: 1. Birth weight, weaning weight, and wool production - Lemma, S.; Awgichew, K.; Worku, G.; Kitila, A.; Fletcher, I. (1989)
Purebred Menz and first cross (50%) Awassi x Menz and 75% Awassi cross sheep were bred and reared under common environmental and management conditions. Mean birth and 120-day weaning weights recorded from 10 lambings were 2.4, 3.0, and 3.8 kg (p<0.001) and 15.6, 17.6, and 21.5 kg (P<0.001) for Menz, 50% Awassi, and 75% Awassi lambs respectively. Mean annual greasy wool weights recorded over three years were 0.60, 0.98, and 1.33 kg (p<0.001) for Menz, 50% Awassi, and 75% Awassi ewes respectively. Thus under the conditions of this investigation birth weights, weaning weights, and annual greasy wool weights all continued to increase with increasing levels of Awassi blood in the crosses.